LINGUISTIC-STATISTICAL ANALYSIS OF WORD FORMATION IN LINGUISTICS - Unarova Dilafruz Abdimajit Qizi (International Scientific and Current Research Conferences, 2025)
In this article, the morphological structure of words in the Buryat language, especially the processes of suffix formation, is analyzed using linguistic and statistical methods using the literary texts of G.A. Dirkheeva. In the study, based on a large text corpus compiled from the works of Kh. Namsarayev, words were divided into morphemes, and their frequency, functional load, and variety of formation were studied. In addition, the stages of linguostatistical analysis of homonym grammatical forms were described and the methodology used in this direction was described. The article creates important theoretical and practical foundations for linguostatistical research.